The Role of English Films in Language Learning: A Theoretical Perspective on Listening Comprehension Development - Fuad, Nurul (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
This study aims to explore the potential of English films as authentic media for developing listening skills among learners of English as a Foreign Language (EFL). In the EFL context, listening plays a foundational role in the acquisition of other language skills. The research adopts a qualitative approach using library research methods, drawing on relevant literature and previous studies as the basis for analysis. The findings indicate that films provide authentic linguistic input, including features such as intonation, accent, idiomatic expressions, and everyday conversational language. Moreover, the visual components of films—such as facial expressions, body language, and social settings—enhance listening comprehension more effectively than conventional materials. These observations are supported by theories such as Dual Coding and Multimedia Learning, which emphasize the importance of integrating verbal and visual elements in the learning process. Nevertheless, the implementation of film-based listening instruction presents certain challenges, including speech rate, cultural differences, and the need for contextually appropriate task design. Therefore, the use of films in listening pedagogy must be carefully planned to align with learning objectives and learner needs